Digital Literacy at Pornographic Content and Parent’s Assistance of Early Childhood - Ayun, Primada Qurrota; Santoso, Hedi Pudjo; Naryoso, Agus; Nugroho, Adi; Yuliyanto, Muh. (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The use of gadgets in the pandemic era is unavoidable. Distance learning system makes children from an early age to the final-year age use gadgets and online media as a means of information and education. Unfortunately, the data shows that children are accidentally exposed to and susceptible to pornographic content in online media. This makes children need communication and parental assistance in accessing online media. This research was conducted in Semarang private school as a form of community dedication for parents who have an early child. The theory used in this study is the theory of family communication patterns and parental mediation theory. The research method used is mixed methods. The results of this study indicate that parents give their children access to gadgets by giving them screen time. Every respondent also felt concerned about pornographic content. They stated that there is a need for assistance when early childhood access gadgets. Communication in the form of conversation and active mediation between parents and children is a form of parental communication in preventing exposure to pornographic content in online media.